1977
DOI: 10.1070/pu1977v020n02abeh005331
|View full text |Cite
|
Sign up to set email alerts
|

Ion-beam plasma and the propagation of intense compensated ion beams

Abstract: A small protein was self-assembled on a template. A metal-binding ligand, 4.4-dicarboxylic acid-Z,Z-bipyridine, was attached to the N-terminus of an oligopeptide with the potential to form an amphiphilic a-helix. These bipyridine-modified peptides trimerized to form a three or-helix bundle protein in the presence of FE(ii). The cumulative binding constant was determined to be > 5 x 10'' M-'. approximately 25 times greater than that of a control compound with no peptide moiety. Aldehyde templates are being deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 1 publication
0
17
0
Order By: Relevance
“…The presence of cold, "fresh" plasma in the beam path provides the minimum space-charge potential and the best option for neutralized ballistic focusing. Experimental studies of ballistic transverse focusing have confirmed that the best neutralization results are achieved when volumetric plasma is used everywhere along the beam path to assure robust charge neutralization 43,44 . Hence, in the following we only study the case when a large amount of cold background plasma is available everywhere along the beam path.…”
Section: Iid Neutralization By a Volumetric Plasmamentioning
confidence: 85%
See 1 more Smart Citation
“…The presence of cold, "fresh" plasma in the beam path provides the minimum space-charge potential and the best option for neutralized ballistic focusing. Experimental studies of ballistic transverse focusing have confirmed that the best neutralization results are achieved when volumetric plasma is used everywhere along the beam path to assure robust charge neutralization 43,44 . Hence, in the following we only study the case when a large amount of cold background plasma is available everywhere along the beam path.…”
Section: Iid Neutralization By a Volumetric Plasmamentioning
confidence: 85%
“…Neutralization and focusing of intense charge particle beams by background plasma form the basis for a variety of applications to high-energy accelerators and colliders, 1,2,3 astrophysics 4,5,6,7 , inertial confinement fusion, in particular, fast ignition 8 and heavy ion fusion, 9,10,11,12 magnetic fusion based on field-reversed configurations fueled by energetic ion beams 13 , the physics of solar flares 14 , highintensity high-energy particle beam propagation in the atmosphere and outer-space plasmas 15 , as well as basic plasma physics phenomena 16 . For instance, one of the modern approaches to ion beam compression for heavy ion fusion applications is to use a dense background plasma which charge neutralizes the ion charge bunch, and hence facilitates compression of the charge bunch against strong space-charge forces 9,10,17,18,19,20 .…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies of ballistic transverse focusing have confirmed that the best results are achieved when both a plasma plug and a bulk plasma are used for charge neutralization. 8,11 Hence, in the following we only study the case when a large amount of cold background plasma is available everywhere on the beam path.…”
Section: Introductionmentioning
confidence: 99%
“…For longer ion pulses, the plasma ion response may effect the plasma return current. 11,31,32 The organization of this paper is as follows: In Sec. II, the basic equations and model are discussed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation